An earth observation potential evaluation model and its application to SDG indicators - Meng Jin; Ming Lin; Yufu Liu; Yuqi Bai (International Journal of Digital Earth, 2022)
Thousands of satellites and instruments are providing very unique long-term, refined, and diverse perception capabilities for the states and changes of the Earth's surface environment. When leveraging Earth Observation (EO) techniques in SDG monitoring in specific regions, an important prerequisite is to evaluate whether EO could meet user requirements in terms of spatial coverage, temporal frequency and observing variables or objects. It is highly expected to have a quantitative model that can not only represent EO capabilities and observation requirements but also evaluate the potential of EO capability to fulfil these requirements. This paper first describes EO capabilities from the satellite's orbit, operation time, spatial resolution, revisit cycle, accessibility and observation relevance level to variables. Observation requirements and priorities are then derived from SDG indicators. Finally, the potential model is established to match EO capabilities and user requirements. Taking SDG 14.1.1 as an example, this model is capable of returning an ordered list of satellites and instruments for users to refer to. This model meets the gap of evaluating EO potential to fulfil SDG monitoring. It could make full use of the available EO capabilities worldwide to meet SDG indicator monitoring requirements.